Students’ Perception oysn Teacher’s Teaching Speaking Through Indonesian Comedian Photos: Persepsi Siswa tentang Guru Berbicara Melalui Foto Komedian Indonesia - Ab. Aziz Bin Sulaiman (LPPM Institut Studi Islam Sunan Doe, 2022)
Teaching speaking to the English learners is an essential skill to teach. It is required a typical way of teaching by selecting such an exciting instructional. Many ways might be used to do. One of them is by using an outstanding photos. However, the current reality showed that most of the students’ skill of speaking were very low. It was proved by lack of students’ participation when they responded the topic of the lesson taught. In line with this problem, the purpose of this research was to determine the students’ perception on teacher’s teaching speaking through indonesian comedian photos. The research question in this research was “what is the students’ perception on teacher’s teaching speaking through indonesian comedian photos in MA NW Wanasaba?” This research was categorized as descriptive qualitative research. It was conducted in MA NW Wanasaba. The number of the subject were 20 students as respondents.To get the data, the present researcher used participant observation and interview. The technique in analyzing the data used descriptive analysis by collecting the obtained data from both participant observation and interview. To sum up the finding of obtained data from those instrumets, there were a total of 20 respondents participating in the interview which mostly came from the students of MA NW Wanasaba in which the interview was successfully conducted. From the result, the present researcher drew an inference that the students’ perception on teacher’s teaching speaking through indonesian comesian photos was positivelywelcomed.